2019
DOI: 10.1186/s12889-019-6619-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and health outcomes of domestic violence amongst clinical populations in Arab countries: a systematic review and meta-analysis

Abstract: BackgroundAn estimated 30% of women worldwide experience intimate partner violence (IPV) during their lifetime. Exposure to IPV is associated with poor health outcomes and the prevalence of violence may be higher amongst women seeking healthcare. Existing evidence from the Arab region is limited. We conducted a systematic review and meta-analysis of prevalence and health outcomes of domestic violence (IPV or violence from a family member) in clinical populations in Arab countries.MethodsUsing terms related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
43
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 48 publications
4
43
0
3
Order By: Relevance
“…This observational study's community setting, in routine general practice, with borough-wide implementation, with the IRIS effect not significantly different in the four implementation boroughs with diverse populations, makes its results generalisable to similar settings in the UK and potentially to comparable primary care systems in highincome countries. For lower-income countries [30], this healthcare response to DVA is modifiable, if the health setting is safe, using existing community resources if DVA service infrastructure is absent.…”
Section: Discussionmentioning
confidence: 99%
“…This observational study's community setting, in routine general practice, with borough-wide implementation, with the IRIS effect not significantly different in the four implementation boroughs with diverse populations, makes its results generalisable to similar settings in the UK and potentially to comparable primary care systems in highincome countries. For lower-income countries [30], this healthcare response to DVA is modifiable, if the health setting is safe, using existing community resources if DVA service infrastructure is absent.…”
Section: Discussionmentioning
confidence: 99%
“…), physicians and other healthcare practitioners may be at the frontline of intervening and supporting survivors of DV. 2 Providing healthcare professionals with training on identifying signs and intervening in a culturally sensitive manner may prove to be beneficial, especially in regards to referring survivors to seek out mental health resources. Mental health interventions focusing on increasing hope may act as a protective factor, particularly against suicidal risk, as found by researchers studying the role of hope as a mediator between IPV and suicide risk among Turkish women.…”
Section: Stigma Against Psychotherapy In Middle Eastern Culturesmentioning
confidence: 99%
“…This prevalence is raised to 37% in Eastern Mediterranean countries [1,2]. A recent systematic review showed that a doubling of this lifetime prevalence (70%) was reported among Arab women attending health care settings in Arab countries [3].…”
Section: Introductionmentioning
confidence: 99%